Design of optical surfaces conform the hyperbolic Monge-Ampère equation - Bertens M.W.M.C.; Anthonissen M.J.H.; IJzerman W.L.; ten Thije Boonkkamp J.H.M. (EPJ Web of Conferences, 2022)
We present a method for designing freeform optical surfaces for illumination optics. By the laws of reflection, refraction and conservation of energy, a fully nonlinear PDE, the Monge-Ampere equation, is derived for the optical surface. By the edge ray principle a transport boundary condition is obtained. We solve the hyperbolic variant of the PDE using a least-squares method, resulting in optical saddle surfaces for a parallel source and far-field target.